Monte Carlo Simulation and Reconstruction: Assessment of Myocardial Perfusion Imaging of Tracer Dynamics With Cardiac Motion Due to Deformation and Respiration Using Gamma Camera With Continuous Acquisition - Huh, Yoonsuk; Shrestha, Uttam M.; Gullberg, Grant T.; Seo, Youngho (Frontiers in Cardiovascular Medicine, 2022)
Purpose: Myocardial perfusion imaging (MPI) with single photon emission computed tomography (SPECT) is routinely used in the stress lab. Recently, our group extended its potential going from 3D visual analysis to 4D spatiotemporal reconstruction of dynamically acquired data to capture the time variation of the radiotracer. However, the quality of the image is compromised due to cardiac deformation and respiration. The work presented here develops an algorithm that reconstructs the dynamic data for the continuous image acquisition with a slowly rotating SPECT camera and evaluates the algorithm with the data using a Monte Carlo simulation. Methods: A clinically realistic Monte Carlo (MC) simulation is developed using Extended Cardiac Torso (XCAT) digital phantom with respiratory and cardiac motion to model continuous data acquisition of dynamic cardiac SPECT with slowly rotating gamma cameras. Reconstruction results are presented showing the dynamics of the tracer in the myocardium as it continuously deforms. These results are then compared with the 4D-spatiotemporal reconstruction method that models only the temporal changes of the tracer activity. Mean Stabilized Activity (MSA), signal-to-noise ratio (SNR), and Bias for the myocardium activities for three different target-to-background ratios (TBR) are evaluated. Results: The MSA and SNR are higher for higher TBR while Biases were improved to less than 10%. The correlation between the exhalation-inhalation sequence with the ground truth during the respiratory cycle was excellent. Conclusion: The continuous image acquisition for a dynamic scan using conventional two-head gamma cameras can provide valuable information to MPI. Our study demonstrated the viability of using the continuous image acquisition method on this system.